(untitled) (Research, Society and Development, 2023)
The south of Brazil has the largest area cultivated for pecan walnut (Carya illinoinensis). In recent years, the crop has shown considerable potential for planting expansion, increased consumption linked to health benefits, in addition to financial return. This work aimed to study the productivity of pecan trees, in southern Brazil, over six years of production with different varieties, Barton, Pitol 1, Cenci, Pitol 2 and Imperial, planted under free standing, with a spacing of 10 x 10 meters. In order to correlate these varieties with the edaphoclimatic factors of the Anta Gorda region in Rio Grande do Sul. The experimental design in the field was completely randomized blocks, with ten replications, in a bifactorial scheme. Factor A composed of the five pecan tree varieties (Barton, Pitol 1, Cenci, Pitol 2 and Imperial) and factor B composed of the six periods (2012, 2013, 2014, 2015, 2016 and 2017). Barton stood out in five harvests, contrasting with the Pitol 1, Cenci, Pitol 2 and Imperial varieties and within each harvest, with a general average productivity of 24.90 Kg plant-1, standing out in the sixth harvest with an estimated productivity of 4,185 Kg ha-1. Following, the Cenci and Pitol 2 varieties deserve to be highlighted, with average harvest values of 13.12 and 11.8 Kg plant-1, respectively, much higher values than the others. With this study it was observed that Barton, Cenci and Pitol 2 maintained their productivity indexes in the edaphoclimatic conditions of Anta Gorda in Rio Grande do Sul, Brazil.